Aktivitas Antibakteri Ekstrak Etanol Biji Tanaman Petai Cina (Leucaena leucocephala (Lam.) de Wit) Terhadap Bacillus subtilis ATCC 6633 - Teonanda, Tiara; Ghozaly, Muchammad Reza; Abna, Inherni Marti (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2024)
Petai cina is a plant that is often used as traditional medicine among the community. This plant has been reported to have pharmacological activity as antibacterial, antidiabetic, anti-inflammatory, anticancer, anthelmintic, antioxidant and larvicide. The seeds of the Chinese petai are often used as a traditional treatment for wounds and swelling. This research aims to determine the antibacterial activity of 96% ethanol extract of Chinese petai seeds against the bacteria Bacillus subtilis ATCC 6633. In this study, extraction was carried out using the ultrasonic assisted method (UAE), testing the antibacterial activity using the agar diffusion method using the well method. The results of phytochemical screening showed that the 96% ethanol extract of Chinese petai seeds contained flavonoids, saponins, tannins and triterpenoids. The 96% ethanol extract of petai china seeds has antibacterial activity against Bacillus subtilis ATCC 6633 which was indicated by the formation of a clear zone around the well. The 96% ethanol extract of petai chinese seeds has moderate antibacterial power against Bacillus subtilis ATCC 6633 with an inhibition zone diameter of between 5 mm-10 mm with 50 μl of extract was taken from various concentrations (300, 350, 400, 450, 500 mg/mL).